Bilateral high division of sciatic nerve - Shwetha, K.; Dakshayani, KR (International Journal of Research in Medical Sciences, 2017)
Sciatic nerve is the thickest nerve in the body formed by the sacral plexus from L4 to S3 in the lesser pelvis. It emerges through the greater sciatic foramen below the piriformis and enter the gluteal region. Then the nerve passes on the back of the thigh and at the level of superior angle of popliteal fossa it terminates by dividing into tibial and common peroneal nerve. The knowledge of anatomical variations in the division of nerve is important for various surgical and anaesthetic procedures. During routine dissection in the department of anatomy, Mysore Medical College & Research Institute, Mysore, a rare bilateral high division of sciatic nerve was observed in a female cadaver aged about 40 years. In the present case there was bilateral high division of sciatic nerve. The nerve was seen dividing into two branches before it emerges through the greater sciatic foramen. The tibial nerve was entering the gluteal region below the piriformis muscle and common peroneal nerve was entering by piercing the piriformis. The knowledge of this variation is important as the nerve may get compressed with surrounding anatomical structures resulting in non discogenic sciatica. The awareness of variations is important for surgeons during various procedures like fracture, posterior dislocation of hip joint and hip joint replacement. The anatomical variations are important during deep intramuscular injections in gluteal region and also for anaesthetists during sciatic nerve block.